A Customized Validator Recommender System for PoS Networks Using Similarity-Based Circular Visualization - Lee, Jaeuk; Kim, Jisu; Han, Hyunwoo; Lee, Kyungwon (Proceedings - 2024 IEEE 14th Symposium on Large Data Analysis and Visualization, LDAV 2024, 2024)
This study analyzes the impact of validator behavior on investor rewards in proof-of-stake (PoS) based blockchain networks and proposes a visualization system to assist investors in selecting appropriate validators. This system enables personalized evaluations through five adjustable indicators tailored to the investor's preferences. By utilizing similarity-based circular visualizations and radar charts, it facilitates the selection and comparison of validators. Additionally, it provides time-series data-based line graphs and raw data-based table views to support detailed comparative analysis among validators. The introduction of such a multifaceted evaluation methodology in staking investments is expected to contribute to the formation of user-customized portfolios and the establishment of optimized investment strategies.
Keywords: Block-chain; Blockchain network; Circular visualization; Customized recommendation; Investors' preferences; Linegraph; Radar chart; Similarity-based analyze; Time-series data; Visualization system; Blockchain Networks; Circular Visualization; Customized Recommendations; Similarity-Based Analysis